Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1530/jrf.0.0810175
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of luteal function in dogs by luteinizing hormone antiserum and by bromocriptine

Abstract: Summary. Beagle bitches were treated with equine anti-LH serum (ALHS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
4

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 18 publications
1
55
0
4
Order By: Relevance
“…This suggests that not LH but PRL is closely involved in stimulation of the corpus luteum 25 days after ovulation. This result supports the finding that PRL is a luteotrophic factor in dogs [3,19,21,23].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that not LH but PRL is closely involved in stimulation of the corpus luteum 25 days after ovulation. This result supports the finding that PRL is a luteotrophic factor in dogs [3,19,21,23].…”
Section: Discussionsupporting
confidence: 92%
“…Douglas et al [8] reported that prolactin and luteinizing hormone (LH) are necessary for maintenance of the corpus luteum during postimplantation gestation in mink. Normal luteal function in dogs also requires both prolactin and LH [5,6]. Further studies are required to clarify the immediate trigger of abortion during the active pregnancy period in pinnipeds.…”
Section: Discussionmentioning
confidence: 99%
“…The canine luteal phase can be divided into two periods: i) the early luteal phase, lasting 2-4 weeks of steadily increasing P 4 concentrations, highest proliferation rate and resistance to luteolytic treatments that are effective later in the cycle (Okkens et al 1986, Concannon et al 1987 and ii) the mature-CL portion of phase, during which the CL is more responsive to luteal treatments. Both LH and prolactin (PRL) are luteotrophic (Concannon 1980, Onclin et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Both LH and prolactin (PRL) are luteotrophic (Concannon 1980, Onclin et al 2000. For the mature CL in the second half of dioestrus, PRL becomes the main luteotrophic hormone (Concannon et al 1987, Okkens et al 1990, blocking LH function, however, results only in a transient P 4 decrease (Concannon et al 1987, Onclin et al 2000. Luteal regression, however, is unavoidable and occurs in spite of an increased gonadotrophic support.…”
Section: Introductionmentioning
confidence: 99%